Relationships Among Childhood Maltreatment, Limbic System Dysfunction, and Eating Disorders in College Women - Mercurio, Andrea E. (Journal of interpersonal violence, 2022)
The mechanisms linking childhood maltreatment and eating pathology are not fully understood. We examined the mediating role of limbic system dysfunction in the relationships between three forms of childhood maltreatment (parental psychological maltreatment, parental physical maltreatment, and parental emotional neglect) and eating disorder symptoms. A convenience sample of college women (N = 246, M age = 19.62, SD = 2.41) completed measures of maltreatment (Parent-Child Conflict Tactics Scales and the Parental Bonding Instrument), limbic system dysfunction (Limbic System Questionnaire), and eating pathology (Eating Disorder Examination Questionnaire). We hypothesized that there would be an indirect effect of each type of childhood maltreatment on eating disorder symptoms via limbic system irritability. Results generally supported the hypotheses. Examination of the individual paths that defined the indirect effect indicated that higher reported childhood maltreatment was associated with greater limbic irritability symptoms, and higher limbic irritability symptomatology was related to higher total eating disorder scores. There were no significant direct effects for any of the proposed models. Findings are in line with research supporting the role of limbic system dysfunction as a possible pathway in the maltreatment-eating disorder link. Given that limbic system dysfunction may underlie behavioral symptoms of eating disorders, efforts targeting limbic system dysfunction associated with child maltreatment might best be undertaken at an early developmental stage, although interventions for college women struggling with eating disorders are also crucial.